Over the limit [videorecording (DVD)] - Prus, Marta, 1987-; Mamun, Margarita, 1995- (Film Movement series., 2019)
Elite rhythmic gymnast Margarita Mamun is soon to retire, but has one final goal set out for her: winning Olympic gold. This documentary "looks at the grueling Russian system for training athletes and the intense physical and mental labor put into a sport that thrives on its beautiful aesthetics"--Container.